Whose Rights Count? Negotiating Practice, Policy, and Legal Dilemmas Regarding Infant–Parent Contact When Infants are in Out‐of‐Home Care. Issue 2 (19th February 2013) - Miron, Devi; Bisaillon, Claud; Jordan, Brigid; Bryce, Graham; Gauthier, Yvon; St‐Andre, Martin; Minnis, Helen
Abstract This article takes a human rights perspective with a view to articulating the infant's perspective when the infant has been subjected to abuse, neglect, or both and is reliant on the state to ensure his or her health and well‐being. When a young child is removed from parental care, important and often difficult decisions have to be made about subsequent contact between child and parent. We consider a number of dilemmas which may arise for practitioners when they are assisting child welfare decision makers in relation to contact, and acknowledge the limited empirical follow‐up studies of the impact of child welfare practice and legal decisions on infant outcomes. We draw on the significant and substantive evidence base about infant emotional and cognitive development and infant–parent attachment relationships as well as infant mental health to illuminate the infant's subjective experience in these practice dilemmas. We describe innovations in practice from various countries, which seek to shed light on the challenges often associated with contact.